2017
DOI: 10.1515/bog-2017-0036
|View full text |Cite
|
Sign up to set email alerts
|

Small-area variations in overweight and obesity in an urban area of Nigeria: The role of fast food outlets

Abstract: Abstract. Overweight and obesity are two related health issues of epidemic proportions. In Nigeria, these health conditions have been emerging only recently. The extant literature shows inter-city variations in the prevalence of overweight and obesity in Nigeria. However, they say little about intra-city variations of these health problems in Nigerian urban centres. Thus, the focus of the study was to determine the small-area variations in the prevalence of overweight and obesity in an urban area of Nigeria an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Also, there is limited evidence to guide the implementation of these policies. obesity discovered that for every additional convenience store in poor urban settings in Ghana, there was a 0.2kg/m2 increase in BMI, and every out-of-home cooked food place available, there was a 0.1kg/m2 reduction in BMI of residents while the study by Osayomi and Orhiere (2017) 43 on environmental factors and obesity in Nigeria identified that physical proximity to fast food outlets is a determinant of obesity. See tables 4 and 5 for a summary of the review.…”
Section: Introductionmentioning
confidence: 99%
“…Also, there is limited evidence to guide the implementation of these policies. obesity discovered that for every additional convenience store in poor urban settings in Ghana, there was a 0.2kg/m2 increase in BMI, and every out-of-home cooked food place available, there was a 0.1kg/m2 reduction in BMI of residents while the study by Osayomi and Orhiere (2017) 43 on environmental factors and obesity in Nigeria identified that physical proximity to fast food outlets is a determinant of obesity. See tables 4 and 5 for a summary of the review.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning obesity, some studies based on NHS and surveillance records found a substantial difference in the small-area pattern of obesity rates among adults in high-income countries (11)(12)(13)(14)(15)(16) and in children (17)(18)(19). Since these studies cross-sectionally estimate obesity rates in smaller areas (20,21), there is a gap of knowledge of the increase of obesity rate among adults, especially in a setting where medium-low income households persist.…”
Section: Introductionmentioning
confidence: 99%
“…As Osayomi (2019;1160) puts it, "an obese individual is frequently perceived to be well nourished, financially comfortable and erroneously assumed to live a stress-free life". In other words, a person with a slim frame is portrayed as being impoverished; terminally ill and without dignity (Osayomi and Orhiere, 2017;Pus et al 2016). In addition, the worldviews or social constructions among some racial/ethnic groups such as the Yoruba, Igbo and Efik of Nigeria, glorify large body size (Ibrahim and Jegede, 2017;Oe, 2009;Brink, 1989, Osayomi andOrhiere, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In other words, a person with a slim frame is portrayed as being impoverished; terminally ill and without dignity (Osayomi and Orhiere, 2017;Pus et al 2016). In addition, the worldviews or social constructions among some racial/ethnic groups such as the Yoruba, Igbo and Efik of Nigeria, glorify large body size (Ibrahim and Jegede, 2017;Oe, 2009;Brink, 1989, Osayomi andOrhiere, 2017). For instance, large body size among the Yoruba ethnic group symbolizes Ìfọkànbalẹ (peace of mind) and is often couched in proverbial expressions which connote the cultural acceptance of fatness, such as ara sísan kì s'àrùn (fatness is not illness) (Ibrahim and Jegede, 2017b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation